Game Theory And Its Optimum Application For Solving Economic Problems (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article discusses the application of game theory in economics. Game theory is a branch of mathematical economics. She develops recommendations on the rational action of the participants in the process when their interests do not coincide. Game theory helps enterprises make the best decision in a conflict situation. The focus of the article is game theory a section of mathematical methods for modeling and forecasting the economy related to the implementation of a formal study of social, political, and economic situations in conflict and cooperation. The use of game-theoretic models is able to describe the interaction of several agents participating in game interaction. These agents are traditionally people, groups of people, companies, ministries, or any combination thereof. The introduction of methods and models of game theory into the mathematical training of bachelors and masters of economics is intended to equip future economists with a special language that allows them to efficiently formulate, structure, analyze and simulate strategic scenarios, and make optimal scientifically based decisions in the face of incomplete information and risk